Increased expression of EphA2 and E-N cadherin switch in primary hepatocellular carcinoma. Issue 6 (November 2013) - Fan, Min; Liu, Yu; Xia, Fada; Wang, Zhuolu; Huang, Yun; Li, Jingdong; Wang, Zhiming; Li, Xinying
Aim: To investigate the expression and clinical significance of ephrin type-A receptor 2 and epithelial-mesenchymal transition-related proteins in primary hepatocellular carcinoma. Methods: Tissues from 52 primary hepatocellular carcinomas and 12 human normal liver tissues were detected for expression of ephrin type-A receptor 2, E-cadherin, and N-cadherin by immunochemistry. Cinicopathological features of hepatocellular carcinoma and tumor recurrence after operation were studied for the association with these molecular expressions and E-N cadherin switch. Results: Increased expressions of ephrin type-A receptor 2 and N-cadherin and reduced expression of E-cadherin were significantly detected in hepatocellular carcinoma compared with normal liver tissues. Univariate analysis showed that there were close associations between unfavorable clinicopathological features and expressions of ephrin type-A receptor 2, E-cadherin, N-cadherin, and E-N cadherin switch. Ephrin type-A receptor 2 and E-cadherin expressions were confirmed as independent prognostic factors when corrected with age, gender, AFP, HBsAg, liver cirrhosis, tumor size, nodules, capsule, portal vein invasion, cell differentiation, and TNM stage. Conclusions: The overexpression of ephrin type-A receptor 2 protein is correlated with the number of tumors, capsular integrity, portal vein cancer thrombus and clinical stages. Epithelial-mesenchymal transition regulated by ephrin type-A receptor 2 is involved in the aggressive clinicopathological features and prognosis, suggesting that the receptor may play an important role in the progression and metastasis of hepatocellular carcinoma.